Legal Nature of a Timeshare Contract in Tourist Real Estate: A comparative Study - Joint Search - Kasim Hashim Mahmud; Sabri Karim Sabri (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Our research in this study revolves around the legal nature of the time-sharing contract in tourist real estate, as this contract is a modern contract in the field of tourism and real estate, which is an agreement between two parties, a professional party, the owner of the tourist property in one of the tourist resorts, and another party, who is often a tourist in this The contract, the first party (the professional party) concludes several contracts with several people (tourists) about a specific tourist property in one of the tourist resorts, and the period of use of the property is divided into different periods of time, so that each person benefits from the property according to the period agreed upon in the contract, which is Of the time contracts and of the so-called contracts, which is one of the unnecessary contracts,and it is one of the formal contracts also in some countries. This contract is distinguished with the tourist trip contract and with the real estate development activity, and despite the organization of this contract in several countries, but it has not been regulated so far Neither in Iraq nor in the Kurdistan Region.On this basis, we studied those laws that organized the provisions of this contract, whether through a ministerial decision, as is the case in Egypt, or the issuance of a law, as is the case in the Emirate of Dubai and Tunisia, and we tried within that framework to reach the legal nature selfish for this contract. Finally, we concluded the study with several results and recommendations about the legal nature of this contract.